Hey there! :)
Answer:
Has one solution.
(Graphed below)
Explanation:
***The equations are graphed below, but this can also be solved algebraically.***
Set each equation equal to each other:
-6x + 6 = -3x - 3
Add 6x to both sides:
6 = 3x - 3
Add 3 to both sides:
9 = 3x
x = 3.
Plug in the value of x into an equation to solve for y:
y = -6(3) + 6
y = -18 + 6
y = -12.
The system of equations only has ONE solution at (3, -12).
On the graph, as well, the point of intersection is at (3, -12). This is the solution.